Monitorização Óptica do Desempenho em Sistemas de Comunicações Baseada em Histogramas de Amplitude Assincronamente Amostrados DOI: 10.14209/jcis.2003.16 - S. Andre, Paulo; L. J. Teixeira, A.; J. N. Lima, M.; da Rocha, F.; L. Pinto, J.; Almeida, T.; Pousa, M. (Journal of Communication and Information Systems, 2015)
The performance monitoring in optical networks is a crucial aspect in the deployment of the future transparent photonic networks. In this paper we evaluate the asynchronous Q factor from a dense wavelength division multiplexed optical signal distorted by chromatic dispersion, amplified spontaneous emission noise and non-linear effects. using amplitude histograms. It was experimentally confirmed the asynchronous histogram numerical model developed to estimate the Q factor as function of the signal to noise ratio. rise time and format of the optical pulses. We also propose a model to access directly the bit error rate of a DWDM optical signal, from the asynchronously detected amplitude histograms. The obtained experimental results indicate that this method can monitor the signal performance degradation, confirming the applicability of this technique as optical performance monitor for transparent photonics networks.